Organized Homegardens Contribute to Micronutrient Intakes and Dietary Diversity of Rural Households in Sri Lanka - Thamilini, Joshepkumar; Wekumbura, Chandima; Mohotti, Anoma Janaki; Kumara, Aruna Pradeep; Kudagammana, Sanath Thushara; Silva, K. D. Renuka Ruchira; Frossard, Emmanuel (Frontiers in Sustainable Food Systems, 2019)
A greater diversity of crops grown in homegardens in Sri Lanka is thought to be positively associated with increased nutritional diversity of the diet of members of households and their improved nutritional status and health. However, no studies have been made to evaluate the quantitative contribution of homegardens to people’s food and nutrient intake and security. Here we report three studies to test an improved homegarden production system, with agricultural and extension interventions, designed for the mid-country wet zone in Sri Lanka. The study assessed the impact of the improved system on crop type diversity, on dietary intake and diversity and food and nutritional security of the households. In Study 1, 100 households with homegardens were evaluated for their household characteristics and homegarden practices. Study 2 was on a sub sample of 20 households each with organized homegardens (OHG); households were provided with planting material, agricultural inputs and advice, and were regularly monitored by a field officer for methodical farming. These improved home gardens were contrasted with non-organized homegardens (NOHG; without intervention) to measure crop diversity through a simple species count. Study 3 assessed 25 sample households with OHG and 20 households with NOHG: dietary nutrient intake and diversity and household food security were quantified. Family food consumption was assessed using a 5-day diet diary. Perceived household food security status was determined using United States Department of Agriculture Food Security Module. Nutrient intakes, dietary adequacy and contribution to dietary diversity from produce derived from homegarden were calculated. A total of 149 crop species were recorded in the homegardens with a 14% greater diversity in OHG than NOHG. Household food security was not significantly associated with organized or non-organized homegardens. The improved, organized home gardens provided diets with a greater contribution of energy, carbohydrates, fat, calcium, iron, zinc, folate, thiamin, niacin, vitamin C and vitamin A compared with NOHG. The study demonstrates that households with OHG had greater dietary diversity from homegarden produce compared with that of households with NOHG leading to better food and micronutrient intake and nutritional security.